Home, History, and the Postsecular: A Literary–Religious Inquiry of Disgrace - Dong, Liang (Religions, 2024)
In J.M. Coetzee’s Disgrace, the postsecular emerges as a critical framework to understand the characters’ search for home amidst the remnants of South Africa’s colonial legacy. This essay proposes an exploration of how the novel’s engagement with the postsecular scriptures and moments offers a nuanced perspective on the religious impulse within the literary form. I focus on the protagonist, Lurie, whose journey from a sexual scandal to a commitment to animal welfare symbolizes a broader quest for redemption and atonement. Contrasting Lurie’s postsecular odyssey is his daughter Lucy’s steadfast attachment to her farm, which becomes a battleground for historical racial tensions. Through a mythological critical approach, we interpret Lucy’s experience as a contemporary iteration of the scapegoat, embodying the sacrificial role in a society seeking reconciliation and healing. Our analysis extends to the novel’s esthetic and ethical dimensions, examining how Coetzee’s narrative challenges and reframes traditional religious narratives. By situating our discussion within the fields of the sciences of religions, theology, and mythology, I contribute to the understanding of literature as a vital medium for engaging with religious and theological themes. The essay concludes with a reflection on the implications of Coetzee’s postsecular discourse for the individual’s search for home and belonging in a post-apartheid context.